Impact of vascular density on pancreatic islet viability: a computational study - Félix-Martínez, Gerardo J.; de la Cruz, Lizbeth; Whisman, Daniel; Godínez-Fernández, J. Rafael (Frontiers in Physiology, 2025)
IntroductionPancreatic islets are densely vascularized clusters of cells that secrete insulin, glucagon, and somatostatin, hormones essential to glucose metabolism. The viability and function of islet cells rely on the availability of oxygen and nutrients supplied by islet capillaries. In this work, we developed a computational model of vascularized pancreatic islets, aiming to estimate the proper level of vascularization to ensure cell viability.MethodsThe simulated islets were reconstructed from experimental data of human and mouse, with capillaries generated using a pathfinding algorithm. The number of capillaries required to maintain islet cell viability was determined by analyzing oxygen gradients resulting from cell consumption at 6- and 20-mM glucose concentrations and a varying number of capillaries.Results Our simulations in human and mouse models suggest that >100 capillaries (i.e., vascular density > 5.9%) are required to maintain >96% of cells in a viable state at 6- and 20-mM glucose. From this percentage of viable cells, >75% of cells are in functional state (PO2 > 10 mmHg) at 6 mM glucose while it reduces to ∼50% at 20 mM glucose.DiscussionThese models represent an advancement in computational models available to study islet physiology by incorporating the vascular system to enable more accurate, predictive, and physiologically relevant simulations in health, disease, and bioengineering approaches where changes in the islet vasculature are relevant. To support the broad application of the model, we provide a user-friendly computational tool where the viability of islet cells can be estimated based on a given number of capillaries, islet size and glucose level.